In situ quantitative measurements on MMP-9 activity in single living cells by single molecule fluorescence correlation spectroscopy. Issue 4 (12th January 2023) - Lu, Xintong; Ding, Luoyu; Song, Haohan; Yu, Wenxin; Dong, Chaoqing; Ren, Jicun
Abstract : MMP-9 activity in single living cells under different stimulation conditions was in situ quantitatively measured with fluorescence correlation spectroscopy. Abstract : Matrix metalloproteinase-9 (MMP-9) plays an important role in tumor progression. It is of great significance to establish a sensitive in situ assay strategy for MMP-9 activity in single living cells. Here a novel in situ single molecule spectroscopy method based on the fluorescence correlation spectroscopy (FCS) technique was proposed for measuring the MMP-9 activity at different locations within single living cells, using a fluorescent specific peptide and a reference dye as dual probes. The measurement principle is based on the decrease of the ratiometric translational diffusion time of dual probes in the detection volume due to the peptide cleavage caused by MMP-9. The peptide probe was designed to be composed of an MMP-9 cleavage and cell-penetrating peptide sequence that was labeled with a fluorophore and conjugated with a streptavidin (SAV) molecule. The ratiometric translational diffusion time was used as the measurement parameter to eliminate the effect of intracellular uncertain viscosity. The linear relationship between the ratiometric diffusion time and MMP-9 activity was established, and applied to the determination of enzymatic activity in cell lysates as well as the evaluation of the inhibitory effects of different inhibitors on MMP-9. More importantly, the method was successfully used to dynamically determine MMP-9 activity in single living cells or under the stimulation with phorbol 12-myristate 13-acetate (PMA) and inhibitors.